Study on the effect of adding enzyme in whole-crop corn silage - LU Jian-min; HU Wei-lian; LIU Jian-xin (浙江大学学报. 农业与生命科学版, 2005)
Whole-crop corn was ensiled with an experimental preparation of cell-wall degrading enzymes at four levels respectively: 0 (control, C), 800 (1), 1300 (2), 1800 (3) g/t DM. The result showed that all whole-crop corn silages were well preserved with low pH, low ammonia nitrogen (NH3-N) and high lactic acid content. The fermentation quality showed no significant difference between the four groups. However, addition of enzyme decreased obviously the content of neutral detergent fiber (NDF). Enzyme addition improved the silage's nutritive value by increasing in vitro organic matter digestibility (OMD), in vitro gas production at 48 h (GP48) and in sacco degradation of DM at 48 h incubation (DMD48), and the DMD48 in group 2 was the highest and 15.4% higher than that in the control (P<0.01). In conclusion, the best nutritive value of whole-crop corn silage can be obtained when enzyme was added at the level of 1300 g/t DM.